Measurement in marketing - Malhotra, Naresh K.; Baumgartner, Hans; Weijters, Bert (Review of marketing research, 2022)
Measurement in Marketing is built to provide a state-of-the-art discussion of current topics in measurement and deepen readers' appreciation of the fundamental role of measurement in empirical research in marketing.